Polarity in cuticular ridge development and insect attachment on leaf surfaces of Schismatoglottis calyptrata (Araceae) - Surapaneni, Venkata A.; Aust, Tobias; Speck, Thomas; Thielen, Marc (Beilstein Journal of Nanotechnology, 2021)
The plant cuticle is a multifunctional barrier that separates the organs of the plant from the surrounding environment. Cuticular ridges are microscale wrinkle-like cuticular protrusions that occur on many flower and leaf surfaces. These microscopic ridges can help against pest insects by reducing the frictional forces experienced when they walk on the leaves and might also provide mechanical stability to the growing plant organs. Here, we have studied the development of cuticular ridges on adaxial leaf surfaces of the tropical Araceae Schismatoglottis calyptrata. We used polymer replicas of adaxial leaf surfaces at various ontogenetic stages to study the morphological changes occurring on the leaf surfaces. We characterized the replica surfaces by using confocal laser scanning microscopy and commercial surface analysis software. The development of cuticular ridges is polar and the ridge progression occurs basipetally with a specific inclination to the midrib on Schismatoglottis calyptrata leaves. Using Colorado potato beetles as model species, we performed traction experiments on freshly unrolled and adult leaves and found low walking frictional forces of insects on both of these surfaces. The changes in the micro- and macroscale morphology of the leaves should improve our understanding of the way that plants defend themselves against insect herbivores.
Keywords: cuticular ridges; insect adhesion; leaf surfaces; ontogeny; polarity; surface replication